2015
DOI: 10.1007/s12282-015-0626-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tamoxifen and fulvestrant long-term treatments on ROS production and (pro/anti)-oxidant enzymes mRNA levels in a MCF-7-derived breast cancer cell line

Abstract: When compared to long-term 4-hydroxytamoxifen-treated breast cancer cells, addition of fulvestrant treatment was able to diminish ROS production and p22(phox) mRNA level, and made cells more sensitive to growth inhibition induced by tempol. These effects may be a valuable asset of the fulvestrant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…As ERα expression is lost or decreased in OHTR cells (Al Saleh et al ., ), we next asked whether breast cancer cell resistance to OHTam could be associated with changes in HDAC9 gene expression. Comparison of the HDAC mRNA profile in previously described MCF7 cell lines that are responsive or resistant to OHTam (Badia et al ., , ) showed that among the 11 HDACs analyzed, only HDAC9 expression was significantly higher (7.6 times) in OHTR than in parental OHTam‐responsive cells (Fig. A).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As ERα expression is lost or decreased in OHTR cells (Al Saleh et al ., ), we next asked whether breast cancer cell resistance to OHTam could be associated with changes in HDAC9 gene expression. Comparison of the HDAC mRNA profile in previously described MCF7 cell lines that are responsive or resistant to OHTam (Badia et al ., , ) showed that among the 11 HDACs analyzed, only HDAC9 expression was significantly higher (7.6 times) in OHTR than in parental OHTam‐responsive cells (Fig. A).…”
Section: Resultsmentioning
confidence: 93%
“…Similar results were obtained with OHTR T47D (Mishra et al ., ) (Fig. B) as well as in other MCF7 cell lines (Brünner et al ., ; Eric Badia et al ., ; Gonzalez‐Malerva et al ., ) (Fig. A,B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the ROS is the major risk factor for the development and progression of breast cancer. To determine the antioxidant potential of the formulation, levels of ROS were estimated by using the 2,7-Dichlorofloresin diacetate (DCFDA) method [ 58 ]. This was performed in a 96-well culture plate seeded with 2 × 10 5 MCF 7 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…Tamoxifen’s main application is the treatment and/or prevention of breast cancer most frequently occurring among post-menopausal women, but this drug proved to be applicable for the treatment of infertility both in women and men [ 2 , 3 ], or for the prevention of gynecomastia [ 4 ]. Aside from Tamoxifen’s SERM activity explored in the indications listed above, its function in the generation of Reactive Oxygen Species (ROS) is also well-documented concerning adverse effects [ 3 , 5 ]. ROS including, e.g., superoxide anion and hydroxyl radicals, are involved in signal transmission pathways regulating cell growth, differentiation, survival, inflammation and immune response.…”
Section: Introductionmentioning
confidence: 99%